Theories Explaining Stock Price Behavior: A Review of the Literature - Ruhani, Fatima; Islam, Md. Aminul Islam; Tunku Ahmad, Tunku Salha (International Journal of Islamic Banking and Finance Research, 2018)
Estimation of stock price behavior is important for several reasons and for different stakeholders in the market. Many studies are trying to put forward theories to explain this phenomenon and more still have tried to use these theories in order to predict future changes in prices. The growing linkages of national markets in currency, commodity and stock with world markets and the existence of common players, have given stock price behavior a new property – that of its speedy transmissibility across markets. The present study aims to review the existing literature of the theories explaining stock price behavior. To review the literature, this study presented the theories in two different eras. First era is the pre modern era in financial theory and the second one is the theories in modern financial economics with technological development